Retinoblastoma - Current Diagnostic Strategies, Treatment Approaches and Long-term Outcomes - Witowska-Jeleń, Ewa; Pogrzebielski, Arkadiusz (British Journal of Healthcare and Medical Research, 2026)
Retinoblastoma is the most common primary intraocular malignancy of childhood and remains a significant cause of visual impairment, ocular morbidity, and mortality worldwide. Although survival rates have improved substantially in developed countries, delayed diagnosis continues to adversely affect visual and systemic outcomes. This review provides an updated overview of the current understanding of retinoblastoma, including its epidemiology, genetic background, clinical presentation, classification systems, diagnostic strategies, and contemporary treatment approaches. Particular attention is given to the importance of early clinical signs, especially leukocoria and strabismus, which may represent the first manifestation of the disease and facilitate timely diagnosis. Recent advances in eye-preserving therapies, including intra-arterial chemotherapy, intravitreal chemotherapy, focal treatment modalities, and modern imaging techniques, have significantly improved globe salvage and visual outcomes. In addition, the review discusses the long-term ophthalmological, systemic, psychological, and social consequences of retinoblastoma and its treatment. Early recognition, prompt referral, multidisciplinary management, genetic counselling, and long-term rehabilitation remain essential components of care and contribute substantially to improving survival, visual function, and quality of life in affected children.